Late-Holocene floodplain development, land-use, and hydroclimate–flood relationships on the lower Ohio River, US ... - Broxton W Bird; Barr, Robert C; Commerford, Julie; Gilhooly, William P; Wilson, Jeremy J; Finney, Bruce; McLauchlan, Kendra; G William Monaghan (Figshare, 2019)
Floodplain development, land-use, and flooding on the lower Ohio River are investigated with a 3100-year-long sediment archive from Avery Lake, a swale lake on the Black Bottom floodplain in southern Illinois, US. In all, 12 radiocarbon dates show that Avery Lake formed at 1130 BCE (3100 cal. yr BP), almost 3000 years later than previously thought, indicating that the Black Bottom floodplain is younger and more dynamic than previously estimated. Three subsequent periods of extensive land clearance were identified by changes in pollen composition, corresponding to Native American occupations before 1500 CE and the current Euro-American occupation beginning in the 18th century. Sedimentation rates prior to 1820 CE changed independently of land clearance events, suggesting natural as opposed to land-use controls. Comparison with high-resolution paleoclimate data from Martin Lake, IN, indicates that lower Ohio River flooding was frequent when cold-season precipitation originating from the Pacific/Arctic ...